Ken Kesey's 'One Flew over the Cuckoo's Nest: the sardonic representation of power and authority in nurse Ratched - Scerri, Mariella (Research and Humanities in Medical Education, 2020)
Critical acclaim and popular opinion have elevated Kesey's first novel, One Flew over the Cuckoo's Nest published in 1962, to something of a modern classic, much read and written about as well as adapted for film. Cuckoo's Nest offers an interesting alternative scenario to the usual depictions of the nurse as Angel of Mercy, the unskilled handmaiden or the ministering angel found in literature. In giving Nurse Ratched tyrannical authority, demonising the institution and its representative, Kesey elicits the themes of control, submission and alienation through the structure of nursing and care involved. These same themes also link to gender, representing similar fears of female empowerment and male power rendered impotent by a sterile social structure. This paper aims to analyse the sardonic representation of the power and authority in Nurse Ratched and how gender and the spectacle of masculinity is defined through discourse. This is imperative as literature and the media have a strong influence on public views, shaping the way the public values and treats professions in health care. Nursing is plagued by feminine stereotypes that continue to undermine the profession up till the present day. This reading of One Flew over the Cuckoo's Nest provides educational opportunities to engage in critical dialogue around this and other texts which speak to nursing and human concerns. This will equip nurses with the right tools for discernment so that they can challenge rather than accept how nurses are represented in the literature.